Knockdown of ARHGAP24 reduces intimal hyperplasia through inhibiting the proliferation and phenotypic switching of smooth muscle cells possibly by inactivating both AKT and ERK1/2 signaling pathways - Wei Liu; Jing Han; Qiuping Yang; Luoxing Xia; Cheng Chen; Jie Song; Yao Cai (Biochemistry and Biophysics Reports, 2024)
Intimal hyperplasia is one of the common pathophysiological foundations of vascular remodeling including restenosis and atherosclerosis. The Rho GTPase activating protein 24 (ARHGAP24) has been reported as a tumor suppressor in multiple cancers. Nevertheless, the role of ARHGAP24 in intimal hyperplasia is unclear. Interestingly, our results showed that ARHGAP24 was significantly up-regulated in dedifferentiated VSMC in vitro and vivo, which suggested that ARHGAP24 could promote VSMC dedifferentiation and proliferation. Knockdown of ARHGAP24 effectively inhibited VSMC dedifferentiation and proliferation in the absence and present of PDGF-BB, which might inactivate both ATK and ERK1/2 signaling pathways. Moreover, AAV9-mediated silencing of Arhgap24 also alleviates VSMC dedifferentiation and proliferation in the wire-injured mouse femoral arteries, contributing to reducing neointima formation. AAV9-mediated overexpression of Arhgap24 exacerbates intimal hyperplasia. We demonstrate that decreased ARHGAP24 expression restrained VSMC proliferation and dedifferentiation possibly by inactivating both AKT and ERK1/2 signaling pathways, which may provide a potential therapeutic strategy for diseases associated with intimal hyperplasia including restenosis and atherosclerosis.